The Portrayal of Family Relationship in ‘Otherhood’ Movie - Lambok Hermanto Sihombing; Syafa Azzahra Putri Andini (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
Every film depicts its unique subject matter and values to the real world. The concept of "Otherhood" illustrates the issue of family estrangement, which is one of the issues that society faces. It represents both the indicators of separation and the audience-observable causes of estrangement. It also depicts a jocasta complex, a reverse Oedipus complex on a parent. Although "Otherhood" contains such weighty subject matter, it is constructed with relatable dialogues and enjoyable yet engrossing sequences for the audience; these two elements are examined in this paper to determine the representation of family estrangement.